A Study on Career Aspirations of Undergraduates in Sri Lanka - Ratnayake, R. M. C. S.; Elvitigala, D. Y. C (Faculty of Commerce and Management Studies University of Kelaniya, Sri Lanka, 2020)
Studying career aspiration among undergraduates has become an important topic since undergraduates face numerous challenges after completing their university degree especially when seeking for suitable employment opportunities. This study investigates the “career aspiration” in the context of current Sri Lankan Undergraduates, identify the factors that affect different career aspirations of undergraduates and the key issues faced by undergraduates regarding their career aspirations separately. To achieve the research objectives, the study was devised using descriptive qualitative approach. Data were collected from 50 undergraduates in 04 solitary universities as per the sample and from 03 graduates to conduct case studies based on their successful stories for validation purpose through semi structured interviews. The analysis of collected data is done by thematic analysis method by using NVivo 8 qualitative analysis software. The results of the study indicated that the subjective norms, perceived behavioral control and attitude are the factors which affect different career aspirations of the undergraduates in Sri Lanka. In most situations attitude had a positive relationship with the career aspiration, and it had an influence on other two constructs. Finally, key issues were identified as lack of experiences, competition, political changes, and lack of monetary facilities and all the respondents agree with the statement that the identified issues become great influence to career aspiration. This research is a significant source for the policy makers and decision makers in manipulating the university education system of the island and the universities can meaningfully contribute towards career development of undergraduates.
Keywords: Career Aspiration, Attitudes, Social norms, Perceived behavioural control, Undergraduates